The Colonial Scramble and Its Aftermath: Writing Public Histories of the Postcolonies of Socialism - Serguei Alex. Oushakine (eSamizdat)
Using a brief summary of the development of postcolonial studies and anticolonial thought as its main backdrop, the essay explores how postcolonial imagination finds its representations in various public history projects in contemporary Kyrgyzstan. By linking public history and postcolonial thought, the essay demonstrates that the production of historical narratives from below, by non-professional historians, is rarely motivated by strictly historical goals. Indeed, publicity here is a tool for subjecting historical materials to a process of deep recycling. The past is mined for forms, plots, events, and connections, which, then, enable ‘public historians’ to create and circulate stories about the present. As a result, various historical projects not only (re)establish links with previously inaccessible historical periods, but also they effectively change the public context in which non-professional historians situate themselves. Historical knowledge here is public in its form and postcolonial in its content. Relying on Kyrgyz cinema and scholarly publications, the essay identifies two separate but interrelated postcolonial discourses – the ‘poetics of orphanhood’ and the ‘politics of belonging’. It argues that these two public languages of self-description are structured around the same themes of origin and relatedness. Each discourse problematizes these topics in its own way, but both discourses are intertwined in an intriguing symbolic dialogue.